2014
DOI: 10.15309/14psd150211
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Lifestyles in Old Age: Effects of Psycho Educational Intervention With Older Men

Abstract: Este artigo está licenciado sob uma licença Creative Commons Atribuição-NãoComercial 4.0 Internacional. Você tem direito de:Compartilhar -copiar e redistribuir o material em qualquer suporte ou formato.Adaptar -remixar, transformar, e criar a partir do material. De acordo com os termos seguintes:Atribuição -Você deve dar o crédito apropriado, prover um link para a licença e indicar se mudanças foram feitas. Você deve fazê-lo em qualquer circunstância razoável, mas de maneira alguma que sugira ao licenciante a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
10

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 32 publications
0
8
0
10
Order By: Relevance
“…Only two studies (Murta and Tróccoli, 2009;Pinheiro et al, 2006) reported clear in the text whether the loss of participants and/or the data lost was correctly addressed, or at least that the quality of the data had been reviewed before statistical analysis. All studies reported results in line with the objectives proposed, despite seven studies having reported the variables of interest for this review as secondary outcome measures (e.g., Borges and Seidl 2014;Coelho and Murta, 2007;Cuadra-Peralta et al, 2012;Murta and Tróccoli, 2009;Pivaral et al, 2015;Pureza et al, 2012;Rocha et al, 2013). The majority of studies published achieved good standards in terms of methodology quality.…”
Section: Methodology Qualitymentioning
confidence: 82%
See 4 more Smart Citations
“…Only two studies (Murta and Tróccoli, 2009;Pinheiro et al, 2006) reported clear in the text whether the loss of participants and/or the data lost was correctly addressed, or at least that the quality of the data had been reviewed before statistical analysis. All studies reported results in line with the objectives proposed, despite seven studies having reported the variables of interest for this review as secondary outcome measures (e.g., Borges and Seidl 2014;Coelho and Murta, 2007;Cuadra-Peralta et al, 2012;Murta and Tróccoli, 2009;Pivaral et al, 2015;Pureza et al, 2012;Rocha et al, 2013). The majority of studies published achieved good standards in terms of methodology quality.…”
Section: Methodology Qualitymentioning
confidence: 82%
“…The number of medium-quality papers which included pre-post evaluations is modest to only four studies including a psycho-education intervention for self-care of elderly males in Brazil (Borges and Seidl, 2014); a social skills educative training for parents of children with behavioural problems in Brazil (Pinheiro et al, 2006); a social skills training for university students with social anxiety/phobia in Brazil (Pureza et al, 2012); and a brief behavioural intervention for the management of emotional states of teachers in Chile (Vera-Villarroel et al, 2005). Only one medium-quality paper used follow-up study at T2 (four months) and reported improvement in Assertiveness and Empathy following a psycho-education intervention (Borges and Seidl, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations